Association of South-East Asian Nations-US Stock Market Associations in and Around US 2007-09 Financial Crisis: An Autoregressive Distributed Lag Application for Policy Implications - Dasgupta, Ranjan (International Journal of Economics and Financial Issues, 2017)
This study examines portfolio diversification and arbitrage opportunities available to international investors in 16 Asian and US stock markets by using most advanced autoregressive distributed lag methods in and around recent US sub-prime crisis of 2007-09 with selected structural breaks. Results show that in overall and during-the-crisis period these markets were co-integrated in long-run and there were not enough portfolio diversification opportunities for international investors like other sub-periods. The Indian and Chinese markets were strongest contenders among Asian and US to attract foreign inflows. In short-run, these markets show dynamic adjustments generally within 1 month which neutralizes arbitrage opportunities. Keywords: Asian and US Stock Markets, Autoregressive Distributed Lag, Co-integrations, Market Efficiency, Portfolio Diversification, US 2007-09 Crisis JEL Classifications: C32, G15